VIRCATOR - ANALYTICAL AND NUMERICAL ANALYSIS AND OPTIMIZATION OF A VACUUM MICROWAVE HIGH POWER DEVICE - Wymysłowski, Artur (International Journal of Research -GRANTHAALAYAH, 2018)
Vircator is a vacuum microwave device characterised by a pulse working signal and high power. It is classified as a High-Power Microwave (HPM) device and often is a component of Electromagnetic Pulse (EMP) weapons and microwave power transmissions. The direct source of a microwave signal is an oscillation of the so-called virtual cathode. The goal of the presented research was to apply analytical analysis and numerical prototyping methods as a methodology for optimization of the electrical and mechanical design taking into account transformation of electrons’ energy into a microwave signal. One of the key drawbacks of viractors as a microwave source is a low energy efficiency transformation, which is typically of a single percentage.